Von Katterburg zu Schönbrunn Die Geschichte Schönbrunns bis Kaiser Leopold I. - Hassmann, Elisabeth (2004)
In 1996, the Palace and Gardens of Schönbrunn were inscribed on the World Heritage List. In inscribing Schönbrunn, the World Heritage Committee of UNESCO recognised that "the Palace and Gardens of Schönbrunn in Vienna - as a symbol of great heritage and one of the most important corner-stones in the history of Austria - are of outstanding universal value", according to Mounir Bouchenaki, director of the UNESCO World Heritage Centre.